MENUMBUHKAN SIKAP PEDULI LINGKUNGAN DALAM PEMBELAJARAN BERDIFERENSIASI BAHASA INGGRIS DENGAN TEKS NARASI - Erna Pujiasih (Jurnal Riset Daerah, 2025)
Best practices in differentiated English learning by reading 'Narrative' with an environmental theme aims to apply the ability to understand the contents of narrative texts of students. This method uses qualitative descriptive. Data obtained based on observations, implementation of learning and questionnaires. The subjects of this study were students of class X of SMA Negeri 1 Bantul. Based on the best practices in the learning carried out, namely showing narrative story videos, explaining the 'Narrative' material, group activities with differentiated task activities, group presentations. Based on the results of the questionnaire and differentiated learning practices, students can understand the material easily, foster an attitude of caring for the environment, being creative, communicative, sharing, cooperation and effective in learning. Learning to read narrative texts, students learn how to analyze narrative texts, increase language skills, various learning methods, collaborate in groups, foster environmental awareness and positive attitudes.